2004
DOI: 10.1182/blood-2003-09-3294
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics of primitive hematopoietic cell populations reveals differences in expression of proteins regulating motility

Abstract: Lineage-marker depleted (Lin ؊ ) murine bone marrow cells expressing stem cell antigen 1 (Sca-1) were sorted on the basis of stem cell factor receptor (c-kit) expression to obtain Lin ؊ Sca ؉ Kit ؉ or Lin ؊ Sca ؉ Kit ؊ cells. Lin ؊ Sca ؉ Kit ؊ cells have a markedly greater chemotactic response to stromal derived factor-1 (SDF-1). Using a novel fluorescent stain, we show that both populations generate similar levels of a key messenger, phosphatidylinositol 3,4,5 trisphosphate (PIP 3 ), in response to SDF-1. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…However, we have previously shown that the ratio of specific mRNAs in LSK ϩ and LSK Ϫ cells does not directly correlate to the ratio of some protein levels present. 16 We therefore analyzed changes seen at the proteome and the mRNA level (generated using microarray technology, see "Materials and methods" for details). This was performed for all of the proteins where there were differences between LSK ϩ and LSK Ϫ cells and for 374 unchanging proteins, which were chosen based on their having been ascribed a Swiss-PROT, TrEMBL, or RefSeq database accession number by the protein analysis software.…”
Section: Resultsmentioning
confidence: 99%
“…However, we have previously shown that the ratio of specific mRNAs in LSK ϩ and LSK Ϫ cells does not directly correlate to the ratio of some protein levels present. 16 We therefore analyzed changes seen at the proteome and the mRNA level (generated using microarray technology, see "Materials and methods" for details). This was performed for all of the proteins where there were differences between LSK ϩ and LSK Ϫ cells and for 374 unchanging proteins, which were chosen based on their having been ascribed a Swiss-PROT, TrEMBL, or RefSeq database accession number by the protein analysis software.…”
Section: Resultsmentioning
confidence: 99%
“…The CCD camera used in this study was automated and fully accessorized with the necessary filters and UV transilluminator to visualize each of these stains. A similar instrument, the Typhoon 8600 was also in fairly widespread use during this decade [253,254].…”
Section: Equipment Innovationsmentioning
confidence: 99%
“…CAPG binds the end of actin filaments and regulates cellular structure (23). Scinderin (adseverin) cleaves actin filaments and has been shown previously to be changed in expression in the hematopoietic stem cell to progenitor cell transition (24). Vimentin is a member of the intermediate filament family of proteins that is increased in expression with all PTKs except FIP1/PDGFR␣.…”
Section: Fig 3 Analysis Of Potential Oncogene Relationshipsmentioning
confidence: 99%